Law Enforcement against Perpetrators of the Crime of Smuggling Imported used Clothes according to Positive Law - Mahendra Akbar Rachmadhani (Universitas Muhammadiyah Surakarta, 2024)
The action of a person to possess goods using clandestine methods that are contrary to statutory regulations is called smuggling. In Indonesia, the crime of smuggling imported used clothing often occurs. This incident occurred due to encouragement from the Indonesian people to have a high interest in foreign products at lower prices. From the act of smuggling imported second-hand clothes, they are able to reap greater profits, thus attracting the interest of individuals involved in smuggling activities. On this occasion, the author uses a normative juridical method based on the perspective of Indonesian positive law, also uses a qualitative descriptive type of research with data analysis techniques based on literature studies by reviewing books and linking literature related to the issues raised in this journal. The perpetrators of criminal cases involving smuggling of imported second-hand clothing cannot be taken lightly, the need for law enforcement for these criminal acts. Stricter supervision is carried out in areas where goods enter from abroad by the government, law enforcement officials and customs agencies. The crime of smuggling has an impact on reducing the country's income and growth, so strict law enforcement is needed against the perpetrators. Together with existing laws and regulations to protect against smuggling, we will then be able to implement these regulations optimally together with the government.